Improving sustainability in indirect procurement by managing sustainability-related uncertainty - Vuohijoki, Niilo (My University, 2023)
Sustainability is an emerging theme in supply chain management and has affected the way how organizations do their procurement. Execution of sustainability in procurement has been studied before, but literature lacks the perspective on challenges and mechanisms suitable for indirect procurement specifically. Indirect procurement faces several challenges different to direct procurement, such as management of heterogeneous categories and numerous small suppliers. Therefore, the mechanisms suitable for management of sustainability might differ. This study aims to fill that gap in the literature and to help organizations to implement wider range of mechanisms to pursue sustainability. Theoretical background of this study stems from Information Processing Model. According to the model organizations face sustainability-related uncertainty, which causes considerable sustainability risks. The model recognizes two groups of methods to reduce sustainability-related uncertainty: Information processing needs reducing mechanisms and Information processing capacity increasing mechanisms. With these mechanisms organizations can manage sustainability-related uncertainty and improve their sustainability performance. The research is conducted as a qualitative multi-case study and answers the research question "How can sustainability be improved in indirect procurement by managing sustainability-related uncertainty?" The conclusions are derived from previous literature and results of this study. The data of this study is collected with semi-structured interviews from indirect procurement professionals working in organizations with recognized sustainability performance. In total, 9 interviewees from 7 organizations participated in this research. The data is analysed using the grounded theory approach. In indirect procurement three kinds of sustainability-related uncertainties were recognized: task uncertainty, source uncertainty and supply chain uncertainty. To tackle these challenges mechanisms partly familiar from previous procurement literature were recognized. In indirect procurement the cooperation and coordination of activities with suppliers and other external parties was considered important. Especially when facing efficiency problems, external audits and sustainability mechanisms embedded into daily processes were considered keys to success. Additionally, organizational culture and attitudes are of utmost importance when implementing sustainability in indirect procurement.

Kestävyys (sustainability) on nouseva teema toimitusketjun hallinnassa ja se on vaikuttanut siihen, miten organisaatiot tekevät hankintojaan. Kestävyyden toteuttamista hankinnoissa on tutkittu runsaasti, mutta kirjallisuudessa ei ole keskitytty haasteisiin ja mekanismeihin epäsuorien hankintojen ympäristössä. Epäsuorissa hankinnoissa on suorista hankinnoista eroavia haasteita, kuten laaja kirjo erilaisia hankintakategorioita ja suuri määrä pieniä toimittajia, ja siksi kestävyyden hallintaan sopivat mekanismit voivat olla erilaisia. Tämä tutkimus pyrkii täyttämään tämän aukon kirjallisuudessa. Tämän tutkimuksen teoreettinen tausta juontuu Information Processing Model -mallista. Mallin mukaan organisaatiot kohtaavat kestävyyteen liittyvää epävarmuutta, mikä aiheuttaa merkittäviä kestävyyteen liittyviä riskejä. Malli tunnistaa kahdenlaisia menetelmiä kestävyyteen liittyvän epävarmuuden vähentämiseksi: informaationkäsittelytarpeen vähentämismekanismit ja informaationkäsittelykapasiteetin lisäämismekanismit. Näillä mekanismeilla organisaatiot hallitsevat kestävyyteen liittyvää epävarmuutta ja parantavat kestävyyssuorituskykyään. Tutkimus on toteutettu laadullisena monitapaustutkimuksena Se vastaa tutkimuskysymykseen: Miten kestävyyttä voidaan parantaa epäsuorassa hankinnassa hallitsemalla kestävyyteen liittyvää epävarmuutta? Johtopäätökset johdetaan aiemmasta kirjallisuudesta sekä tämän tutkimuksen tuloksista. Tutkimuksen aineisto kerätään puolistrukturoiduilla haastatteluilla eri vastuullisuusteemojen parissa menestyneiden organisaatioiden epäsuorien hankintojen ammattilaisilta. Tutkimukseen osallistui yhteensä yhdeksän haastateltavaa seitsemästä organisaatiosta. Aineisto analysoidaan grounded theory -menetelmään pohjautuen. Epäsuorissa hankinnoissa tunnistettiin kolmenlaista kestävyyteen liittyvää epävarmuutta: hankittaviin tuotteeseen, niiden toimittajiin ja toimitusketjuihin liittyvää epävarmuutta. Näiden kaikkien hallitsemiseksi tunnistettiin mekanismeja, jotka osin ovat yhtenäisiä kirjallisuudestakin tuttujen suorien hankintojen mekanismien kanssa. Epäsuorissa hankinnoissa yhteistyön niin toimittajien kuin muiden ulkoisten tahojen kanssa koettiin olevan merkittävässä asemassa. Etenkin tehokkuushaasteiden parissa työskennellessä ulkoiset audit-palvelut ja yhtenäisten prosessien koettiin olevan avain asemassa. Myös organisaation sisäisellä kulttuurilla ja asenteilla on merkittävä rooli kestävyyden toteuttamisessa
Keywords: Sustainability, indirect procurement, sustainability-related uncertainty, ESG, green supply chain management